Highly Diverse Arenaviruses in Neotropical Bats, Brazil - Bentim Góes, Luiz Gustavo; Fischer, Carlo; Almeida Campos, Angélica Cristine; de Carvalho, Cristiano [UNESP]; Moreira-Soto, Andrés; Ambar, Guilherme [UNESP]; da Rosa, Adriana Ruckert; de Oliveira, Debora Cardoso; Jo, Wendy Karen; Cruz-Neto, Ariovaldo P. [UNESP]; Pedro, Wagner André [UNESP]; Queiroz, Luzia Helena [UNESP]; et al. (My University, 2022)
We detected arenavirus RNA in 1.6% of 1,047 bats in Brazil that were sampled during 2007–2011. We identified Tacaribe virus in 2 Artibeus sp. bats and a new arenavirus species in Carollia perspicillata bats that we named Tietê mammarenavirus. Our results suggest that bats are an underrecognized arenavirus reservoir.